2020
DOI: 10.20546/ijcmas.2020.910.426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar Application of Zinc and Boron on Growth and Yield of Mungbean (wilczek) (Vigna radiata L.)

Abstract: A Pot experiment was carried out entitled "Effect of foliar application of Zinc and Boron on growth and yield of Mungbean" (wilczek) (Vigna radiata L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The highest number of branches was obtained under combine foliar application of zinc 0.5% + boron 0.1% and followed by Zinc 0.5%, boron 0.1% and control treatment. Verma et al [18] reported the similar result. This enhancement could be attributed to the promotional effects of micronutrients on vegetative growth, ultimately leading to increased photosynthetic activity.…”
Section: Number Of Branches Plant -1supporting
confidence: 56%
“…The highest number of branches was obtained under combine foliar application of zinc 0.5% + boron 0.1% and followed by Zinc 0.5%, boron 0.1% and control treatment. Verma et al [18] reported the similar result. This enhancement could be attributed to the promotional effects of micronutrients on vegetative growth, ultimately leading to increased photosynthetic activity.…”
Section: Number Of Branches Plant -1supporting
confidence: 56%
“…The plants from each treatment were drawn for different analyses. Plant growth parameters like plant height, plant weight and number of leaves were calculated at different time interval [12,13].…”
Section: Plant Growth Parametersmentioning
confidence: 99%